1997
DOI: 10.1021/ja9630755
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Electrochemical/Chemical Synthesis of Supported, Luminescent Semiconductor Nanocrystallites with Size Selectivity:  Copper(I) Iodide

Abstract: β-CuI nanocrystallites (NCs) are synthesized on the atomically smooth graphite basal plane surface using a new hybrid electrochemical/chemical (E/C) method. This method involves the following steps:  (1) electrochemical deposition of copper NCs onto an electrode surface, (2) electrochemical oxidation of these copper NCs to yield Cu2O, and (3) displacement of oxygen in Cu2O by iodide in an aqueous KI solution. Dispersions of CuI NCs having mean diameters ranging from 10 to 180 Å were prepared using the E/C meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 36 publications
6
80
0
Order By: Relevance
“…Sasha Gorer investigated the effect of decoupling on the PL emission properties of cadmium sulfide nanocrystals prepared using the E/C method. Typically, the PL emission lines which are observed for thousands of E/C-synthesized CuI 20 and CdS 23 nanocrystals are 50-150 meV wide (i.e., the full width taken at half the maximum intensity). Shown in Figure 6, for example, is a PL emission spectrum for approximately 300 000, 80-Å-diameter CdS nanocrystals having a width of 125 meV.…”
Section: "Decoupling" For Improved Particle Size Monodispersitymentioning
confidence: 99%
“…Sasha Gorer investigated the effect of decoupling on the PL emission properties of cadmium sulfide nanocrystals prepared using the E/C method. Typically, the PL emission lines which are observed for thousands of E/C-synthesized CuI 20 and CdS 23 nanocrystals are 50-150 meV wide (i.e., the full width taken at half the maximum intensity). Shown in Figure 6, for example, is a PL emission spectrum for approximately 300 000, 80-Å-diameter CdS nanocrystals having a width of 125 meV.…”
Section: "Decoupling" For Improved Particle Size Monodispersitymentioning
confidence: 99%
“…The advantages of electrodeposition compared with other techniques include low process temperature, low cost and capability of controlling orientations, morphologies and chirality of the deposited films [14][15][16][17][18]. Penner and co-workers have shown that CuI quantum dots can be grown through hybrid electrochemical/chemical method [19]. Other solution-phase based methods have also been explored to grow CuI-based thin films, such as chemical solution [20,21] and hydrothermal synthesis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the characteristic states of the films can be easily controlled by varying the preparation conditions, such as potential, current density, temperature, and pH used during the electrolysis. Until now, high-precision oxide films, such as epitaxial [8,9], superlattice [10], quantum dot [11,12] and noble metal doped films [13] have been prepared by the electrochemical method.…”
Section: Introductionmentioning
confidence: 99%